The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jum.14493
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler Ultrasonography and Shear Wave Elastography as Complementary Imaging Methods for Suspected Local Breast Cancer Recurrence

Abstract: Power Doppler US is unsuitable for discrimination between local breast cancer recurrence and fibrosis. Although the SWE score and SWE maximum elasticity can make this discrimination, the use of these methods to determine biopsy may lead to poorer clinical outcomes than the current practice of performing biopsies of all suspicious masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
2
Order By: Relevance
“…However, evidence regarding the value of SWE in differentiating benign postoperative changes in the breast from local carcinoma recurrences is scarce. A PubMed search performed in October 2019 resulted in only one study that investigated the sensitivity and specificity of SWE in suspected recurrence of breast carcinoma [19]. This study included 29 patients with 32 masses and although it was shown that SWE can discriminate between benign and malignant lesions, it was not recommended to perform biopsies based on SWE results only.…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence regarding the value of SWE in differentiating benign postoperative changes in the breast from local carcinoma recurrences is scarce. A PubMed search performed in October 2019 resulted in only one study that investigated the sensitivity and specificity of SWE in suspected recurrence of breast carcinoma [19]. This study included 29 patients with 32 masses and although it was shown that SWE can discriminate between benign and malignant lesions, it was not recommended to perform biopsies based on SWE results only.…”
Section: Resultsmentioning
confidence: 99%
“…Es gibt jedoch nur wenige Belege für den Stellenwert der SWE bei der Differenzierung zwischen gutartigen postoperativen Mammaveränderungen und malignen Lokalrezidiven. Eine im Oktober 2019 durchgeführte PubMed-Literatursuche ergab nur eine Studie, in der die Sensitivität und Spezifität der SWE bei Rezidivverdacht eines Mammakarzinoms untersucht wurde 19 . Diese Studie umfasste 29 Patienten mit 32 Raumforderungen, und obwohl gezeigt wurde, dass die SWE zwischen benignen und malignen Läsionen differenzieren konnte, wurde nicht empfohlen, Biopsien allein auf Grundlage der SWE-Ergebnisse vorzunehmen.…”
Section: Diskussionunclassified
“…Nosso valor de corte para Vmax é maior do que aquele encontrado na maioria dos estudos publicados, que varia de 2.03 a 4.5 38,48,49,55,56 , mas semelhante ao encontrado por Golatta e colaboradores 37 Dentre os estudos utilizando a tecnologia SSI, os resultados quanto ao melhor parâmetro a ser utilizado são divergentes: Emax para alguns autores [40][41][42]62,63 , Eratio para outros 43,61 O único estudo publicado até o momento avaliando a aplicabilidade da elastografia VTIQ como método complementar na avaliação de recidivas demonstrou que a elastografia auxilia na identificação de nódulos malignos. Entretanto, deixar de realizar a biópsia em caso de suspeita de recidiva pode levar a desfechos ruins e piorar o prognóstico das pacientes 66 . Dessa forma, considerando também os aspectos clínicos, em que as duas suspeitas de recidiva teriam sido biopsiadas, apenas um caso de CDIS dentro de um fibroadenoma não teria sido diagnosticado (0.4% de todos os casos de câncer).…”
Section: Discussionunclassified